The Representations and Implications of Gender Stereotypes Portrayed in Three Selected TV Advertisements Shown in Bangladesh: Critical Interpretation - Shafi, Saheeh (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2021)
This paper aims at a precise critical interpretation of gender roles portrayed in the three selected TV advertisements shown in Bangladesh. The analysis begins with the theoretical framework of gender roles analysis here in this paper: Goffman's Gender Stereotypes Hypothesis which is used to identify and analyse the thematic features present in the ads. After critically examining the hypothesis, Kress and Van Leeuwen's Systemic Functional Analysis framework is used to analyse the semiotic feature to interpret the signs and symbols. After that, Fairclough's stylistic analysis of Discourse Analysis is used to find out these features in the advertisements to search the cultural, political implications. Lastly, the paper uses Pope's The Rape of the Lock and it's Cultural-Ecofeminist Analysis of Francois d'Eaubonne to connect with the above mentioned frameworks from a contextual point of view to predict the future progression of the gender representations and their implications in the coming years whether the changes in gender roles both in houses and workplaces, women empowerment, more female entrepreneurs in the working forces will bring out about a change in the minds of people about the stereotypes and make a more women inclusive and women friendly environment in Bangladesh and South Asian Countries.